Vetores de mudança dos usos da terra e naturalidade da área de entorno da Floresta Nacional de Três Barras (SC) - Moraes Cavaliere, Mayra Cristina Prado de (2017)
Anthropic activities generate impacts to the environment, among them, the biodiversity loss is highlighted. Protected Areas have emerged as a way to protect the remaining biodiversity, but they suffer from external pressures present mainly in their surrounding. Therefore, the aim of this research was to analyze the effects of land use changes in relation to naturalness that configures the scenarios of the ecological sustainability condition of the Três Barras National Forest (Flona de TB) surrounding area among the, years 1986, 1997, 2011, and 2016, in order to understand the cumulative impacts of the anthropogenic activities that induced changes in the Flona’s buffer zone. We used images from the LandSat satellite of the years 1986, 1997, 2011 and 2016 and identified the land use cover by screen vectoring in a Geographic Information System environment. Based on the results of the land use and cover we obtaines the transition matrices between the intervals of the years 1986-1997; 1997-2011; 2011-2016 and 1986-2016. These procedures were developed in ArcGIS 10.2 software. An analysis was made regarding the area and frequency of native forest patches in each year, and the connectivity between these patches was evaluated using the Conefor Sensinode 2.2 software. The analysis of natural condition of the surrounding area of the Flona TB’s buffer zone was carried out using the Urbanity Index (UI) in IDRISI software. The results of connectivity of the forest patches and naturalness were processed statistically in software R to test the null hypothesis of similarity. During the 30 years studied, there were oscillations between the percentage of agricultural, urban and natural areas, evidencing that there is a tendency in the expansion of anthropic areas and loss of native forest. Over the years, natural patches have become less connected in the matrix. The expansion of agricultural areas is based on the driver forces related to public policies, socioeconomics, region history and the environmental characteristics of the Flona TB’s buffer zone. The scenarios of the natural condition presented oscillations between the years 1986 and 2016, with loss of high naturalness areas over the time, indicating that the buffer zone is in a gradual process of ecological sustainability loss due to the increase of the agricultural anthropic areas and decrease of natural areas. The understanding of the driving forces that act in the Flona TB’s buffer zone can be an essential ally for taking measures by the decision makers that increase the connection between the natural patches of the Flona and the buffer zone, ensuring ecological sustainability and the ecosystem services provision.